Pengaruh Kompensasi, Iklim Kerja, dan Kepemimpinan Terhadap Kepuasan Kerja dan Kinerja Karyawan - Manner Tampubolon (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to analyze the effect of compensation, leadership, and work climate on employee performance mediated by job satisfaction. This study uses a descriptive quantitative approach with data sourced from 284 respondents obtained by survey techniques using a questionnaire. The data is analyzed with a Path Analysis approaches helped by SmartPLS. The results of this study indicate that compensation, leadership and organizational climate directly affect Job Satisfaction. Compensation and leadership also have a direct influence on employee performance, but the work climate has no effect on employee performance. Compensation, leadership and work climate have a direct effect on employee performance. Meanwhile, job satisfaction only acts as a mediating variable on the effect of compensation on employee performance.